Patients' rationale for declining participation in a cancer‐associated weight loss study. Issue 2 (13th March 2014) - Wanger, Tammy; Foster, Nathan R.; Nguyen, Phuong L.; Jatoi, Aminah
Abstract : Background: Fewer than 5 % of cancer patients participate in clinical research. Although this paltry rate has led to extensive research on this topic, previous studies have not sought verbatim comments in a real‐time, comprehensive manner to understand why patients decline. Methods: This study used a low‐risk, non‐interventional parent study that focused on cancer‐associated weight loss to understand patients' reasons for declining research participation. A research assistant wrote down the name and verbatim reason of all patients who declined to participate. These comments with accompanying patient demographic data are the subject of this report. Results: Of the 334 patients, 51 (15 %) declined parent study enrollment; three comment‐related themes emerged: (1) a repelling sense of too much institutional research, (2) overwhelming personal health issues, and (3) a low likelihood of returning to the institution. In univariate and multivariate analyses, only age (older) and gender (female) were associated with non‐enrollment. Interestingly, 41 patients with fatigue scores of 7 or worse and 26 with pain scores of 7 or worse were enrolled. Conclusions: Although many factors were associated with declining to participate in research, symptom severity was not. Upfront education might help cancer patients better prioritize their participation in research, particularly as some patients felt overwhelmed by too much research in the institution; and for now, investigators should continue to keep asking patients for their participation.